Implementation of the Regional Government Information System (SIPD) Policy in Order to Improve Regional Government Accountability (Study: General Bureau of the Regional Secretariat of the East Java Provincial Government) - Permatasari, Ayu Widyatama; Handoko, Rudy; Ibnu, Achluddin (Riwayat: Educational Journal of History and Humanities, 2025)
The local government information system (SIPD) policy is a service for managing local development information, local financial information, and other local government information in an integrated and sustainable manner. This policy also brings information disclosure to the public, where through the SIPD policy guarantees every individual to be able to access local government information according to community needs effectively and easily. This study aims to examine how the implementation of the local government information system (SIPD) policy in improving local government accountability in the General Bureau of the Regional Secretariat of East Java Province. The method used in this research is a qualitative method with descriptive analysis and data collection obtained through interviews and research observations. The results showed that the implementation of the regional government information system (SIPD) policy at the General Bureau of the Regional Secretariat of East Java Province has been running and implemented well. However, in its implementation there are still several obstacles that hinder the implementation of the policy. The inhibiting factor found in this research is that the service system facilities provided by the Ministry of Home Affairs (Kemendagri) often experience trouble. This happens because of the surge in national access by OPDs nationally at certain times to the regional government information system. (SIPD) service.